Basic statistics applied to aerobiology - Galan, Carmen (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
To properly collect, organize, summarize and analyze data an investigator needs an efficient sampling method. Another key requirement is proper presentation of data (numeric or graphic). The paper describes basic statistical methods and their possible use in the field of aerobiology.